Proposal for Improvement of Customer Service Operations in a Spare Parts Company (LACCEI, 2024)
The objective of this research is to propose the implementation of a methodology to improve operations in a company that sells spare parts to improve the quality of customer service specifically in the counter area. The research was focused on finding factors and causes that affect the company, through interviews, application of engineering tools, analysis, and observation, it was determined that the lack of a computer system, inventory organization and process design affected the quality of service. Therefore, it was concluded that the Management by Objectives methodology, together with the implementation of the recommendations, will provide the necessary organization to improve the customer service area, allowing to focus the effort on meeting objectives, goals and execute processes efficiently.